2021
DOI: 10.1002/vetr.28
|View full text |Cite
|
Sign up to set email alerts
|

Estimating antimicrobial usage based on sales to beef and dairy farms from UK veterinary practices

Abstract: Background: Accurate estimation of antimicrobial use (AMU) is important in assessing reduction of agricultural AMU. This cross‐sectional study aimed to evaluate several approaches for estimating AMU at the herd level and to report on AMU for beef and dairy farms in Scotland. Methods: Pharmaceutical sales data for 75 cattle herds (2011‐2015) were screened for antimicrobial products and aggregated by herd and year. Several denominators for usage estimates were calculated and compared for their suitability at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(58 reference statements)
2
3
0
Order By: Relevance
“…Farmers indicated mastitis as the main reason for AMU and penicillin as the most used antibiotic, as reported by previous studies in the UK and Scotland [12,35]. However, in the scenarios section, we found similar results to Jones and co-workers: antibiotics were most frequently chosen as a treatment option in calf pneumonia, followed by clinical mastitis [11].…”
Section: Discussionsupporting
confidence: 90%
“…Farmers indicated mastitis as the main reason for AMU and penicillin as the most used antibiotic, as reported by previous studies in the UK and Scotland [12,35]. However, in the scenarios section, we found similar results to Jones and co-workers: antibiotics were most frequently chosen as a treatment option in calf pneumonia, followed by clinical mastitis [11].…”
Section: Discussionsupporting
confidence: 90%
“…Farmers indicated mastitis as the main reason for AMU and penicillin as the most used antimicrobials, also reported by previous studies in the UK and Scotland [14,33]. Instead, in the scenarios section, we found that antimicrobials were most frequently chosen as a treatment option in calf pneumonia, followed by clinical mastitis.…”
Section: Discussionsupporting
confidence: 67%
“…In other words, an estimated 95% of Irish cows received DCT at drying off in 2019. In-lactation antimicrobial usage compares favorably with competitor countries, including the UK where reported usage is 0.59 DCDvet per cow per year ( 70 ). In contrast, reported national dry-cow antimicrobial usage in the UK, including 0.55 ( 70 ) and 0.68 DCDvet per cow per year ( 71 ), is considerably lower than in Ireland.…”
Section: The Evidence Consideredmentioning
confidence: 99%
“…In-lactation antimicrobial usage compares favorably with competitor countries, including the UK where reported usage is 0.59 DCDvet per cow per year ( 70 ). In contrast, reported national dry-cow antimicrobial usage in the UK, including 0.55 ( 70 ) and 0.68 DCDvet per cow per year ( 71 ), is considerably lower than in Ireland. In Ireland, almost all in-lactation therapies and approximately 40% of dry-cow therapies contain critically important antimicrobials (CIAs) ( 19 ) and there has been an increase in usage of highest priority CIAs [HP-CIAs, essentially equivalent to EMA category B (“Restrict”) antimicrobials] in dry-cow therapies in recent years ( 66 ).…”
Section: The Evidence Consideredmentioning
confidence: 99%